Rescue of primary ubiquinone deficiency due to a novel COQ7 defect using 2, 4–dihydroxybensoic acid. Issue 11 (17th June 2015) - Freyer, Christoph; Stranneheim, Henrik; Naess, Karin; Mourier, Arnaud; Felser, Andrea; Maffezzini, Camilla; Lesko, Nicole; Bruhn, Helene; Engvall, Martin; Wibom, Rolf; Barbaro, Michela; Hinze, Yvonne; et al.
Abstract : Background: Coenzyme Q is an essential mitochondrial electron carrier, redox cofactor and a potent antioxidant in the majority of cellular membranes. Coenzyme Q deficiency has been associated with a range of metabolic diseases, as well as with some drug treatments and ageing. Methods: We used whole exome sequencing (WES) to investigate patients with inherited metabolic diseases and applied a novel ultra-pressure liquid chromatography—mass spectrometry approach to measure coenzyme Q in patient samples. Results: We identified a homozygous missense mutation in the COQ7 gene in a patient with complex mitochondrial deficiency, resulting in severely reduced coenzyme Q levels We demonstrate that the coenzyme Q analogue 2, 4-dihydroxybensoic acid (2, 4DHB) was able to specifically bypass the COQ7 deficiency, increase cellular coenzyme Q levels and rescue the biochemical defect in patient fibroblasts. Conclusion: We report the first patient with primary coenzyme Q deficiency due to a homozygous COQ7 mutation and a potentially beneficial treatment using 2, 4DHB.